Motivation to quit or reduce gambling: Associations between Self-Determination Theory and the Transtheoretical Model of Change. Issue 1 (2nd January 2016) - Kushnir, Vladyslav; Godinho, Alexandra; Hodgins, David C.; Hendershot, Christian S.; Cunningham, John A.
ABSTRACT: Motivation for change and recovery from addiction has been commonly assessed using the Transtheoretical Model's stages of change. Analogous to readiness for change, this measure of motivation may not recognize other elements of motivation relevant to successful change. The aim of this study was to examine the relationship between stages of change and reasons for change according to the Self-Determination Theory among problem gamblers motivated to quit. Motivations for change were examined for 200 adult problem gamblers with intent to quit in the next 6 months (contemplation stage) or 30 days (preparation stage). Analyses revealed that higher autonomous motivation for quitting gambling predicted greater likelihood of being in the preparation stage, whereas those with higher external motivation for change were less likely to be farther along the stage of change continuum. The findings suggest that autonomous motivations relate to readiness for quitting gambling, and may predict successful resolution from problem gambling.